Comparative Study of the Thermal Stability of Cinnamon and Oregano Essential Oils from Cinnamon and Oregano After Heat Treatment - Angela Maria Picolloto; Angela Maria Ariati; João Marcos Azevedo Gomes dos Santos; Lidaiane Mariah Silva dos Santos Franciscato; Milene Ribeiro da Silva; Paulo Rodrigo Stival Bittencourt; Otavio Akira Sakai; Cristiane Mengue Feniman Moritz (Orbital: The Electronic Journal of Chemistry)
Essential oils (OEs) are extracted from aromatic plants and are complex mixtures of compounds mainly generated from terpenoids, benzenes, aromatic rings, and phenolic acids. They possess various features that make them valuable as raw materials in diverse industrial and agricultural fields. The main objective of this work was to research, compare, and optimize the thermochemical stability of commercial cinnamon (Cinnamomum verum) and oregano (Origanum vulgare) OEs at room temperature and after treatment at temperatures of 40 °C, 60 °C, 80 °C, and 100 °C for one hour. Each heated OE was considered a sample and was stored in two systems (open and closed) during heating. Forty-two compounds were identified in cinnamon OE, while thirty-five compounds were characterized in oregano OE, with the aid of Fourier transform infrared spectroscopy (FTIR-ATR) to examine the functional groups. Thermal stability and enthalpy variations were studied using thermogravimetric analysis (TG), derivative thermogravimetric analysis (DTG), and differential scanning calorimetry (DSC). The findings indicated that cinnamon essential oil demonstrated greater thermal stability against thermovolatilization compared to oregano essential oil. Importantly, the results also suggested that storing the samples in closed containers significantly slows the thermal decomposition of their constituents. This research underscores the importance of thermal stability and proper storage conditions for preserving the quality and efficacy of essential oils.